A left-handed woman : essays - Thurman, Judith, 1946- (Farrar, Straus and Giroux, 2022)
"A collection of essays from Judith Thurman, a writer "blessed with intellectual curiosity, a sharp wit and unwillingness to receive opinions" (The New York Times)"--